Pengaruh Pengungkapan Emisi Karbon, Emisi Karbon dan Kinerja Lingkungan terhadap Biaya Utang dengan Reputasi Perusahaan sebagai Variabel Moderasi - Gina Hamelia Alta; Deni Darmawati (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study was conducted because carbon emission and environmental performance issues have increasingly become important concerns for stakeholders, particularly regarding their implications for corporate risk and cost of debt. This study aims to examine the effects of carbon emission disclosure, carbon emissions, and environmental performance on the corporate cost of debt, as well as to assess the role of corporate reputation as a moderating variable. The sample consists of 154 observations of energy and mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, selected using a purposive sampling technique. The research employs a quantitative approach with multiple linear regression and Moderated Regression Analysis (MRA). The results show that carbon emission disclosure has a negative and significant effect on the cost of debt, while carbon emissions and environmental performance have no significant effect. Corporate reputation does not moderate the relationship between carbon emission disclosure or carbon emissions and the cost of debt but strengthens the negative relationship between environmental performance and the cost of debt. These findings suggest that corporate reputation only moderates the environmental performance aspect, emphasizing the importance of combining strong reputation and good environmental performance to reduce corporate cost of debt.